The Evaluation of Health Administration Management in the National Health Insurance (JKN) Program in Indonesia - Ince Annisah Adawiyah Arifin; Olyvia Rosalia (PT. Anagata Sembagi Education, 2025)
The National Health Insurance (JKN) program, managed by BPJS Kesehatan, has been a pivotal initiative in Indonesia’s healthcare reform since its launch in 2014. With a membership coverage of 98.67% as of September 2024, the program has demonstrated remarkable progress toward achieving Universal Health Coverage (UHC). While previous studies have predominantly focused on financing, patient satisfaction, and the quality of medical services, this research highlights the often-overlooked aspect of health administration management. Effective and integrated administrative processes are essential to ensuring service delivery, claims processing, data management, and overall system accountability. However, the JKN program continues to face challenges such as administrative inefficiencies, overlapping data, lengthy procedures, and limited participant understanding. This study conducts a qualitative evaluation of administrative management in Makassar City a major urban center with a high JKN participation rate and a complex healthcare system. By analyzing the experiences of healthcare providers, administrative personnel, and JKN members, the study identifies key administrative strengths and systemic bottlenecks. Findings from this research aim to inform policy recommendations for improving administrative efficiency, transparency, and responsiveness, thereby strengthening the sustainability and equity of Indonesia’s national health insurance system.